THE EFFECT OF POSITIVE THINKING TRAINING ON ACADEMIC SELF-EFFICACY STUDENTS OF PSYCHOLOGY UIN PALEMBANG - Sri Rezeki; Ulis Mayrosa; Masayu Hamdatul Azizah Luthfiyyah; Fajrina Mazaya; Apriyoga Sukamto; Anisa Malfiro; Bella Maryati; Winny Wulandari Pratiwi; Chendy Meylia; Nadia Jubta (CV. Era Digital Nusantara, 2022)
The methodology in this experimental study aims to examine the effect of positive thinking training to increase the level of academic self-efficacy in students. This research was conducted on 30 students of the Faculty of Psychology UIN Raden Fatah Palembang. In this study, the subjects were divided into two groups, namely the experimental group and the control group. The hypothesis proposed in this study is that there is a difference between the group that was given positive thinking training (experimental) and not given positive thinking training (control). This study uses a Randomized Pre-Post Test Control Group Design. Positive thinking training was conducted in two meetings. This data collection was carried out using the academic self-efficacy scale method which was made in the form of a questionnaire. Then for data analysis, using the technique of Kolmogorov Smirnov, and Shafiro Wilk using SPSS 22 Statistics for Windows. And test the hypothesis by using the Wilcoxon test on SPSS 22 Statistics for Windows. The results of the Wilcoxon hypothesis test showed that there was no significant difference between the experimental and control groups (p = 0.151 > 0.05 ). However, after being given treatment in the form of positive thinking training, there was a significant difference, namely being (p = 0.029 < 0.05 ). Thus, positive thinking can be one way to increase academic self-efficacy in students. Conclusion: There is an effect of positive thinking training on academic self-efficacy for students of the Islamic Psychology Faculty of UIN Raden Fatah Palembang.